Determining the germinative qualities of red clover seed samples with varying biological status - Lesia Levytska; Lesia Baistruk-Hlodan; Oleh Stasiv; Halyna Bilovus; Maria Khomiak (Наукові горизонти)
The development of forage crop varieties that adapt to changing environmental conditions is an effective strategy to mitigate the impact of climate change with minimal losses. Temperature influences both the timing and rate of seed germination, which in turn ensures uniform seedling emergence, compatibility of red clover with other crops, and the ability to exploit optimal sowing conditions. This study aimed to determine the temperature and time required to achieve maximum germination, as well as the range within which germination occurred, for four red clover samples of varying biological status (cultivars, wild and local populations). Germination capacity and energy of red clover samples were assessed according to the standards outlined in DSTU 4138 2002 and DSTU 2949-94 at temperatures ranging from 3°C to 33°C in 10°C increments. It was established that the optimal temperature for the germination of red clover seeds among the four studied samples ranges from 13°C to 33°C on filter paper and from 13°C to 23°C on sand. The research identified the Vytis cultivar as outperforming other samples in all measured parameters when germinated on filter paper, while the Truskavchanka cultivar demonstrated superior traits when germinated on sand. The best germination rates were observed in the wild population at a temperature of 13°C. These findings explain the uneven emergence of red clover samples of varying biological status in collection and breeding nurseries, as observed under field conditions. The results of this study can inform the development of sowing technologies for red clover under various temperature regimes